Percutaneous endoscopic gastrostomy - Tan, Yan Mei; Goh, Khean Lee (Faculty of Medicine, University of Malaya, 1996)
Since the introduction of percutaneous endoscopic gastrostomy (PEG) into clinical practice in 1980, it has emerged as the preferred method of providing long-term enteral nutrition. PEG insertion is a relatively easy and rapid endoscopic procedure, well tolerated and affords significant palliation to patients. It has been shown to be safe and effective, the rate of complication and mortality being acceptably low. However, PEG is not as widely known or accepted here as it is elsewhere. Patients continue to have nasogastric tubes in place for lengthy periods adding to their discomfort and debility.